2020
DOI: 10.1183/13993003.01754-2020
|View full text |Cite
|
Sign up to set email alerts
|

Functional characteristics of patients with SARS-CoV-2 pneumonia at 30 days post-infection

Abstract: We read with great interest the series of cases reported by MO et al. [1], describing pulmonary function after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in hospitalised patients. The authors describe a significant correlation between diffusing capacity of the lung for carbon monoxide (D LCO) and clinically defined pneumonia severity. Lung involvement of varying extent has been found on computed tomography (CT) in at least 80% of patients with SARS-CoV-2 infection [2, 3]. Extensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
180
2
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(214 citation statements)
references
References 9 publications
(7 reference statements)
20
180
2
12
Order By: Relevance
“…One study did not report the gender and mean age of the patients. 23 Five studies reported that between 6% and 18% of patients had a history of smoking, 4 , 6 , 22 , 23 , 24 while two studies did not report this. 10 , 21 Three studies reported respiratory comorbidities, 4 , 6 , 23 including emphysema, 6 asthma, 4 , 6 sarcoidosis, 6 tuberculosis, 23 chronic bronchitis 4 and bronchiectasis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study did not report the gender and mean age of the patients. 23 Five studies reported that between 6% and 18% of patients had a history of smoking, 4 , 6 , 22 , 23 , 24 while two studies did not report this. 10 , 21 Three studies reported respiratory comorbidities, 4 , 6 , 23 including emphysema, 6 asthma, 4 , 6 sarcoidosis, 6 tuberculosis, 23 chronic bronchitis 4 and bronchiectasis.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, seven studies met the criteria for eligibility and were included in the review. 4 , 6 , 10 , 21 , 22 , 23 , 24 The flow chart of the study selection process is shown in Fig. 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…preprint (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in The copyright holder for this this version posted October 8, 2020. ; https://doi.org/10.1101/2020.10.06.20206060 doi: medRxiv preprint 6 A blood test was performed in 102 (94.4%) of the COVID-19 patients. Table 3 preprint (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in (13). Likewise, the persistence of diffusion alterations seems more common in patients who have severe pneumonia during the acute episode (14).…”
Section: Resultsmentioning
confidence: 99%